Urine Liver-Type Fatty Acid-Binding Protein and Kidney Injury Molecule-1 in HIV-Infected Patients Receiving Combined Antiretroviral Treatment Based on Tenofovir - Jabłonowska, Elżbieta (Mary Ann Liebert, Inc., 2014)
The aim of this study was to determine the presence of kidney tubular damage in the absence of overt evidence of glomerular dysfunction (GFR>60 ml/min without proteinuria) in HIV-infected patients receiving antiretroviral therapy. Urine kidney injury molecule-1 (KIM-1) and liver-type fatty acid-binding protein (L-FABP) levels were measured by ELISA and expressed as a ratio to creatinine. Sixty-six patients (median age 38 years) and 10 healthy controls (median age 35.5 years) were included in the study. Patients with chronic diseases such as diabetes, hypertension, heart disease, or kidney disease were excluded from the study. All patients received tenofovir/emtricitabine combined with one of three other components, namely efavirenz, atazanavir/norvir, or lopinavir/norvir. A lower concentration of L-FABP/creatinine was observed in HIV-infected as compared to healthy individuals (p=0.0353); KIM-1/creatinine was also lower in comparison with healthy controls but not statistically significantly. Patients receiving efavirenz had higher levels of L-FABP/creatinine in comparison to healthy controls (p=0.0039). Patients with anti-HCV had higher concentrations of L-FABP/creatinine as compared to the HIV-monoinfected individuals (not statistically significant) and to healthy subjects (p=0.0356). All four patients with L-FABP>17.5 μg/g creatinine were HIV/HCV coinfected. On multivariate logistic regression urine L-FABP above 5.5 μg/g creatinine was independently associated with body weight (OR=0.93 p=0.039). This study suggests that HIV/HCV-coinfected patients with lower body weight treated with tenofovir may be at an increased risk of tubular dysfunction and should be monitored more closely. The use of protease inhibitors was not associated with an increased risk of tubular disorders.